An efficient event delivery scheme in mobile ad hoc communities. (1st January 2013) - Li, Juan; Khan, SameeUllah; Li, Qingrui
Delivering events and advertisements to interested individuals is an important issue for mobile ad hoc communities. Providing a feasible solution to event delivery in highly dynamic and error prone mobile ad hoc environments is a challenging problem due to the inherent unreliable and unstable nature of mobile ad hoc networks. This paper proposes a novel semantics-based publish/subscribe scheme for efficient event and advertisement delivery in large-scale mobile ad hoc communities. In our proposed publish/subscribe system, mobile nodes are organised into groups and a compact semantics-based indexing is deployed in the groups. Efficient intra- and inter-group routings are proposed to facilitate efficient propagation of event notifications. The effectiveness of the system is demonstrated through a comprehensive set of simulation studies.